Analysis of Non-Performing Loans and Loan to Deposit Ratio - Rachmawati, Rachmawati; A. Sabilalo, Mahmudin; Arif, Sepriansyah Johan (Institut Bisnis dan Informatika Kesatuan, 2024)
Banks are trusted financial institutions that function as intermediary institutions, helping the payment system run smoothly and, no less important, as institutions that are a means of implementing government policies, namely monetary policy. This research aims to determine and analyze the level of bank health using the Non-Performing Loan and Loan to Deposit Ratio methods at PT. Bank Rakyat Indonesia (Persero) Tbk 2019-2022. The type of research used is descriptive research with a quantitative approach. The variables and measurements used in this research consist of Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR). The results of this research show that for 4 periods, starting from 2019 to 2022, the findings were that the results of the bank's health level in terms of the Non-Performing Loan (NPL) ratio and Loan to Deposit Ratio (LDR) were overall healthy.